Late Gothic architecture in Ireland - O'Donovan, Danielle (Trinity College Dublin. Long Room Hub, 2006)
The aim of this research is the recontextualization of Irish late Gothic architecture. The study seeks to isolate the pattern of architectural development within the country and to place it in a broader European architectural setting. The primary research tool is the analysis of moulding profiles, the patterns carved into masonry by those responsible for designing the building.
Exhibited at 'Unlocking the Treasures', a colloquium and poster exhibition to mark the launch of the Long Room Hub on June 14th 2006
Keywords: Architecture -- Gothic; Architecture -- Ireland